Basic Life Support: High School Students’ Knowledge - Indah Dwi Pratiwi; Edi Purwanto (Jurnal Keperawatan, 2016)
Cardiac arrest is considered to be a global health issue that is very important to overcome. The initial rapid assessment and quick response may prevent death or permanent disability. Not only health care workers, but lay person, including the high school students, are expected to be trained in basic life support (BLS). The purpose of this research is to determine if there any influence of basic life support training on the knowledge’s changing amongst high school students. This study was a quasi experimental quantitative research with cross-sectional approach. The sampling technique was a total sampling, with a total number of 32 respondents. Data were analyzed using the Wilcoxon Test. Results showed that there was a changing in the knowledge before and after training of BLS (p-value <0.05), with an average score of knowledge after the training (7.5) was increased significantly compared to the average score of knowledge before the training (5.8). To sum up, giving BLS training is proved to be an effective way to improve high school students’ knowledge about basic life support.